2006
DOI: 10.1021/la060227t
|View full text |Cite
|
Sign up to set email alerts
|

pH-Induced Release from P2VP−PEO Block Copolymer Vesicles

Abstract: The pH-induced release of hydrophilic dyes from poly(2-vinylpyridine-b-ethylene oxide) (P2VP-PEO) block copolymer vesicles is investigated. The structure of the vesicles is characterized using small-angle neutron scattering (SANS) and cryo-electron microscopy (cryo-TEM). A decrease of the pH below 5 leads to protonation and dissolution of the poly-2-vinylpyridine blocks which induces rupture and dissolution of the vesicle membrane. Details of the rupture, dissolution, and release process are studied by fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
118
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(129 citation statements)
references
References 28 publications
6
118
0
2
Order By: Relevance
“…The pK a of such polymers typically indicates the hydrophilic/hydrophobic transition and this value depends on the precise nature of the monomer repeat units. For example, Förster and co-workers reported [94] the pH-induced release of encapsulated dyes from P2VP-based copolymer vesicles at around pH 5. However, the relatively high T g of the P2VP block may not be suitable for delivery applications as this membrane is prone to buckling, which makes such vesicles relatively 'leaky'.…”
Section: Reactive and Environmentally Responsive Membranes For Delivementioning
confidence: 99%
“…The pK a of such polymers typically indicates the hydrophilic/hydrophobic transition and this value depends on the precise nature of the monomer repeat units. For example, Förster and co-workers reported [94] the pH-induced release of encapsulated dyes from P2VP-based copolymer vesicles at around pH 5. However, the relatively high T g of the P2VP block may not be suitable for delivery applications as this membrane is prone to buckling, which makes such vesicles relatively 'leaky'.…”
Section: Reactive and Environmentally Responsive Membranes For Delivementioning
confidence: 99%
“…In contrast to acid catalyzed hydrolysis of the polymer backbone, which occurs on the order of hours to days, pH triggered contents release, using block copolymers whose solubility in aqueous solutions is dependent upon solution pH, can occur much more rapidly [30]. Borchert and colleagues generated polymersomes comprised of poly(2-vinylpyridine)-block-poly (ethylene oxide) (P2VP-b-PEO) copolymers and showed that the resultant vesicles disassemble in acidic solutions and quickly and completely release their contents; this dissolution is due to the protonation of the P2VP block in acidic solutions (below pH 5) which converts the previously hydrophobic block into a water soluble polymer [30].…”
Section: Diblock Copolymers Forming Vesicles and Release Mechanismsmentioning
confidence: 99%
“…Borchert and colleagues generated polymersomes comprised of poly(2-vinylpyridine)-block-poly (ethylene oxide) (P2VP-b-PEO) copolymers and showed that the resultant vesicles disassemble in acidic solutions and quickly and completely release their contents; this dissolution is due to the protonation of the P2VP block in acidic solutions (below pH 5) which converts the previously hydrophobic block into a water soluble polymer [30].…”
Section: Diblock Copolymers Forming Vesicles and Release Mechanismsmentioning
confidence: 99%
“…Moreover, targeted transport can be achieved by taking advantage of the many possibilities to endfunctionalize the copolymers (5). The controlled release of therapeutic substances can also be integrated through the use of copolymers with blocks that respond to chemical stimuli such as hydrolysis (6,7), oxidation (8) or reduction (9) reaction, and pH changes (10)(11)(12)(13)(14)(15)(16)(17). Common strategies have been to use hydrophobic blocks that can progressively degrade or convert into hydrophilic moieties or to use a cleaveable linkage between hydrophobic and hydrophilic blocks.…”
mentioning
confidence: 99%
“…However, in some applications, such as cancer treatment or synthesis of high-value chemicals, a fast and programmed release of entrapped species (drugs, catalysts, or reactants) at a precise site induced by a remote stimulus is desirable to minimize the damage caused by therapeutic agents on the surrounding healthy tissue or to ensure the proper course of the chemical reaction. Although pH- (15,16) and reduction-(9) responsive systems can respond within seconds or minutes, they require that the chemical environment be modified by additional reagents. These environmental changes may not always be compatible with the drug targeting sites or the chemical reaction conditions.…”
mentioning
confidence: 99%